Pattern of xylem phenology in conifers of cold ecosystems at the Northern Hemisphere. (4th May 2016) - Rossi, Sergio; Anfodillo, Tommaso; Čufar, Katarina; Cuny, Henri E.; Deslauriers, Annie; Fonti, Patrick; Frank, David; Gričar, Jožica; Gruber, Andreas; Huang, Jian‐Guo; Jyske, Tuula; Kašpar, Jakub; et al.
Abstract: The interaction between xylem phenology and climate assesses forest growth and productivity and carbon storage across biomes under changing environmental conditions. We tested the hypothesis that patterns of wood formation are maintained unaltered despite the temperature changes across cold ecosystems. Wood microcores were collected weekly or biweekly throughout the growing season for periods varying between 1 and 13 years during 1998–2014 and cut in transverse sections for assessing the onset and ending of the phases of xylem differentiation. The data set represented 1321 trees belonging to 10 conifer species from 39 sites in the Northern Hemisphere and covering an interval of mean annual temperature exceeding 14 K. The phenological events and mean annual temperature of the sites were related linearly, with spring and autumnal events being separated by constant intervals across the range of temperature analysed. At increasing temperature, first enlarging, wall‐thickening and mature tracheids appeared earlier, and last enlarging and wall‐thickening tracheids occurred later. Overall, the period of wood formation lengthened linearly with the mean annual temperature, from 83.7 days at −2 °C to 178.1 days at 12 °C, at a rate of 6.5 days °C −1 . April–May temperatures produced the best models predicting the dates of wood formation. Our findings demonstrated the uniformity of the process of wood formation and the importance of the environmental conditions occurring at the time of growth resumption. Under warming scenarios, the period of wood formation might lengthen synchronously in the cold biomes of the Northern Hemisphere.